Penerapan Teknologi Biogas Berbasis Kotoran Sapi sebagai Upaya Pemanfaatan Energi Terbarukan di Gampong Luthu Lamweu, Aceh Besar - Hisbullah; Mahmuddin; Lukman Hakim; Fahrizal Nasution; Farid Mulana; Yuliana Sy; Aulia Chintia Ambarita; Abubakar (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2026)
The utilization of cattle manure as a renewable energy source represents a strategic approach to enhance energy self-sufficiency in rural areas while promoting sustainable livestock waste management. This community service program was carried out in Gampong Luthu Lamweu, Sukamakmur District, Aceh Besar, by a team of lecturers in collaboration with Gapoktan Al-Falah, BEM FT USK, and the KKN-TEMATIK USK students. The activities encompassed initial program discussions, site surveys and observations, technical planning, socialization, construction of a small-scale biogas reactor, and preparation of feedstock composed of cattle manure, water, EM4 activator, and molasses. Fifteen local participants received hands-on training and mentoring on the operational principles, feedstock management, and maintenance of the biogas system. The system successfully generated biogas, as evidenced by a simple flame test demonstrating a blue flame, and contributed positively to livestock waste management and environmental quality surrounding the cattle pens. The biogas system was formally handed over to village management to ensure its sustainable utilization. Overall, the program demonstrates the effectiveness of collaborative community service in promoting renewable energy adoption, enhancing local technical skills, fostering community empowerment, and supporting environmentally sustainable practices in rural settings.